2019
DOI: 10.1111/geb.12996
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of trait connections across environmental gradients and growth forms

Abstract: Aim Plant trait databases often contain traits that are correlated, but for whom direct (undirected statistical dependency) and indirect (mediated by other traits) connections may be confounded. The confounding of correlation and connection hinders our understanding of plant strategies, and how these vary among growth forms and climate zones. We identified the direct and indirect connections across plant traits relevant to competition, resource acquisition and reproductive strategies using a global database an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 83 publications
6
56
2
1
Order By: Relevance
“…Indeed, for more than two decades studies have suggested that the relationships among plant traits may be visualized as a network or correlogram, and sometimes analyzed using path analysis or structural equation models [21,26,[37][38][39][40][41][42][43]. Recent studies [40,44] have quantified parameters to describe the network topology and the interdependency of traits.…”
Section: Theoretical Basis For Plant Trait Network and Their Numeroumentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, for more than two decades studies have suggested that the relationships among plant traits may be visualized as a network or correlogram, and sometimes analyzed using path analysis or structural equation models [21,26,[37][38][39][40][41][42][43]. Recent studies [40,44] have quantified parameters to describe the network topology and the interdependency of traits.…”
Section: Theoretical Basis For Plant Trait Network and Their Numeroumentioning
confidence: 99%
“…Plant traits can be biologically or statistically correlated; however, not all traits directly connect in all PTNs. Consequently, PTNs with higher edge density, shorter average path length, and shorter diameter imply a stronger coordination among multiple traits [44] (Y. Li, dissertation, Beijing Forestry University, 2020).…”
Section: Trends Trends In In Ecology Ecology and Evolution Evolutionmentioning
confidence: 99%
“…A lack of coupling between these traits is consistent with their contrasting impacts on leaf level function (Li et al, 2015). Indeed, decoupled relationships between leaf economic and hydraulic traits potentially allow greater evolvability for more combinations of leaf traits to adapt to multifarious niche dimensions, resulting in many plant species that coexist within communities in tropical-subtropical forests (Li et al, 2015;Flores-Moreno et al, 2019). Trait-trait relationships represent coordinated ecological strategies and trade-offs of plants, due to the different strategies that could facilitate co-existence (Bruelheide et al, 2018).…”
Section: Adaptation Mechanisms Of Plant Communities and Plant Speciesmentioning
confidence: 81%
“…In this study, we found that the influence of leaf economic-hydraulic trait moments (mean, variance, skewness, and kurtosis) on GPP in observed communities were significantly higher than those in the null communities, indicating that assembly of leaf economic and hydraulic traits within community optimized their productivity. Further, the strong coordination between leaf economic and hydraulic traits at the community level allows plant communities to function efficiently and take up resources faster (Flores-Moreno et al, 2019). This would directly affect ecosystem productivity.…”
Section: The Assembly Of Leaf Functional Traits Within Community Optimentioning
confidence: 99%
See 1 more Smart Citation